2017
DOI: 10.5194/acp-17-1017-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cloud condensation nuclei and ice nucleating particles on precipitation processes and supercooled liquid in mixed-phase orographic clouds

Abstract: Abstract. How orographic mixed-phase clouds respond to the change in cloud condensation nuclei (CCN) and ice nucleating particles (INPs) are highly uncertain. The main snow production mechanism in warm and cold mixed-phase orographic clouds (referred to as WMOCs and CMOCs, respectively, distinguished here as those having cloud tops warmer and colder than −20 • C) could be very different. We quantify the CCN and INP impacts on supercooled water content, cloud phases, and precipitation for a WMOC case and a CMOC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 48 publications
(75 reference statements)
5
83
2
Order By: Relevance
“…Ansmann et al (2009) observed altocumulus clouds which almost always had liquid water at cloud top, suggesting deposition nucleation plays little role. This has been supported by observations in cases of lee-wave clouds (Field et al, 2012) and stratiform clouds (De Boer et al, 2011;Westbrook and Illingworth, 2011), suggesting either immersion or contact freezing dominates ice production.…”
Section: Introductionsupporting
confidence: 59%
“…Ansmann et al (2009) observed altocumulus clouds which almost always had liquid water at cloud top, suggesting deposition nucleation plays little role. This has been supported by observations in cases of lee-wave clouds (Field et al, 2012) and stratiform clouds (De Boer et al, 2011;Westbrook and Illingworth, 2011), suggesting either immersion or contact freezing dominates ice production.…”
Section: Introductionsupporting
confidence: 59%
“…Note that IN form a very small fraction of aerosol particles, and their concentrations are typically over five orders of magnitude less than CCN concentrations. Studies have shown that the IN effect on supercooled water and cloud phase is much more significant than the CCN effect (Fan, Leung, Rosenfeld, & DeMott, 2017).…”
Section: Aerosol Effect On Cloud Microphysicsmentioning
confidence: 99%
“…If the cloud base is high, increasing CCN often suppresses precipitation because smaller droplets reduce riming, which is especially the case for stratiform mixed-phase clouds (Fan et al, 2012A). For orographic mixed-phase clouds, increasing CCN generally suppresses precipitation (Jirak & Cotton, 2006;Rosenfeld & Givati, 2006;Lynn, Khain, Rosenfeld, & Woodley, 2007), but the reverse could happen under extremely polluted conditions due to an invigoration mechanism for orographic mixed-phase clouds (Fan et al, 2017). Other studies show that CCN may not have a significant effect on the total precipitation; rather, they shift precipitation from the windward to leeward slope, a so-called spillover effect Saleeby, Cotton, & Fuller, 2011;Saleeby, Cotton, Lowenthal, & Messina, 2013 For DCC with low cloud bases and weak wind shear, precipitation is intensified by increasing aerosols due to the aerosol invigoration effect (Rosenfeld et al, 2008;Fan et al, 2009Li et al, 2011;Yang & Li, 2014).…”
Section: Precipitation From Deep Cloudsmentioning
confidence: 99%
“…Events like these, both the multiyear drought and subsequent flooding, highlight the importance of understanding the controlling mechanisms for precipitation in this region and improving our ability to forecast changes to these mechanisms. While the availability of condensable water vapor is crucial to the intense rain and snow events associated with ARs (Ralph et al, 2013), the role of aerosol particles, especially those capable of initiating ice crystal formation, is less well understood and has been the focus of recent study (Ault et al, 2011;Creamean et al, 2013;Creamean et al, 2015;Fan et al, 2014;Fan et al, 2017;Martin et al, 2019;Rosenfeld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%